Contributing to the ‘One Health’ framework by exploring the emerging environmental dimensions of antimicrobial resistance from a human geography perspective. - Shenton, Anthony (2023)
The World Health Organization (WHO) states that antimicrobial resistance (AMR) is one of greatest threats to humanity. Some social science research on AMR has focused on the overuse and misuse of antibiotics in hospital and agricultural environments. However, little research has been carried out to explore how ‘environmental publics’ (Eden, 2017) make sense of the emerging environmental dimensions of AMR and how scientists imagine lay publics in relation to those emerging environmental dimensions. Without this information, AMR ‘action plans’ risk failure when put into practice.